On implicit and parametric differentiation

Calculus Level 3

if * f(2x+1)= x.h(2x-5) * and h(1)=2 , h'(1)=4 , then f'(7)= ....


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Apr 11, 2019

Differentiating the above functional equation with respect to x yields:

2 f ( 2 x + 1 ) = h ( 2 x 5 ) + 2 x h ( 2 x 5 ) 2 \cdot f'(2x+1) = h(2x-5) + 2x \cdot h'(2x-5)

Now, h ( 1 ) , h ( 1 ) , h(1), h'(1), and f ( 7 ) f'(7) each occur when x = 3 x = 3 . Substituting the given values for h ( 1 ) , h ( 1 ) h(1), h'(1) gives:

2 f ( 7 ) = h ( 1 ) + 6 h ( 1 ) f ( 7 ) = h ( 1 ) + 6 h ( 1 ) 2 = 2 + ( 6 ) ( 4 ) 2 = 13 . 2 \cdot f'(7) = h(1) + 6 \cdot h'(1) \Rightarrow f'(7) = \frac{h(1) + 6h'(1)}{2} = \frac{2 + (6)(4)}{2} = \boxed{13}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...